90Sr uptake in the freshwater liverwort Riccia fluitans L. - Rubio, L.; Zapico, R.; Fernández, J.A. (My University, 2019)
90Sr is a radioactive isotope of strontium produced by nuclear fission, with a half-life of 28.8 years. This artificial radioisotope is present in natural ecosystems as the results of radioactive fallout from nuclear weapons or releases during nuclear power plants accidents; because of its similarity with Ca*2 is quickly incorporated into the biota. The high mobility of Sr+2 in aquatic compared with terrestrial ecosystems makes the uptake and accumulation of 90Sr+2 higher in aquatic than in terrestrial plants. Here we analyse the uptake rate, kinetics and retention, concentration factor (CF) of 90Sr in the freshwater liverwort Riccia fluiants. 90Sr uptake by R. fluitnas shows a bi-phasic kinetics that fits the Michaelis & Menten model in both micro and milimolar concentration ranges. Apparent semi-saturation constants (KM) were 15 µM and 2 mM for the high and low affinity ranges, respectively. The presence of the K+ channels blocker tetraethyamonium (10 mM TEA) inhibits 90Sr uptake by a 25%. However, the presence of 1 mM La+3 completely inhibits 90Sr uptake in this plant. Maximum incorporation rate occurs at alkaline external pH (8.3), either in plants grown in the presence of K+ or in the absence. Finally, gradual increases of the Ca2+ concentration in the medium progressively inhibits 90Sr uptake. CF values are higher in K+ -deficient plants, CF maximum of 1500, than in K+ -sufficient, (maximum CF of 600) and show similar responses to inhibitors, pH or Ca2+. CF values progressively decrease at increasing external Ca2+ concentrations, higher CF values are found at pH 8.3 but lower values are observed in the presence of TEA, being close to zero in the presence of La+3. The different 90Sr uptake rates in K+-sufficient and K+-deficient plants and TEA sensitivity indicate that one part of 90Sr would be transported through non-selective cation channels. Furthermore, Ca2+ and La3+ sensitivities suggest that 90Sr could be incorporated through Ca2+ channels.
Keywords: Riccia fluitans; Sr uptake; Concentration Factor; Radiostronium